2013
DOI: 10.1159/000353569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphate Binder Therapy on Vascular Stiffness in Early-Stage Chronic Kidney Disease

Abstract: Background/Aims: Cardiovascular disease (CVD) is increased in chronic kidney disease (CKD), and contributed to by the CKD-mineral bone disorder (CKD-MBD). CKD-MBD begins in early CKD and its vascular manifestations begin with vascular stiffness proceeding to increased carotid artery intima-media thickness (cIMT) and vascular calcification (VC). Phosphorus is associated with this progression and is considered a CVD risk factor in CKD. We hypothesized that modifying phosphorus balance with lanthanum carbonate (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 53 publications
3
58
2
1
Order By: Relevance
“…In early CKD, the CKD-MBD is characterized as stimulation of vascular calcification, an osteodystrophy associated with inhibitory signals to bone formation rates, stimulation of osteocytic proteins in the circulation consisting of the hormone FGF23 and sclerostin, and normal serum phosphorus, Ca, and PTH. 11, 13,15,26 Neutralization of a critical renal Wnt inhibitor increased in the circulation by CKD, Dkk1, was sufficient to prevent and treat the vascular calcification (the osteodystrophy) and preserve vascular differentiation. In addition, early changes in phosphate homeostasis were linked to elevated FGF23 levels, thereby completing the pathogenesis of the CKD-MBD.…”
Section: Discussionmentioning
confidence: 99%
“…In early CKD, the CKD-MBD is characterized as stimulation of vascular calcification, an osteodystrophy associated with inhibitory signals to bone formation rates, stimulation of osteocytic proteins in the circulation consisting of the hormone FGF23 and sclerostin, and normal serum phosphorus, Ca, and PTH. 11, 13,15,26 Neutralization of a critical renal Wnt inhibitor increased in the circulation by CKD, Dkk1, was sufficient to prevent and treat the vascular calcification (the osteodystrophy) and preserve vascular differentiation. In addition, early changes in phosphate homeostasis were linked to elevated FGF23 levels, thereby completing the pathogenesis of the CKD-MBD.…”
Section: Discussionmentioning
confidence: 99%
“…13 Given the ability of CKD patients to maintain serum phosphate within the normal range, it is not surprising that single interventions aimed at lowering dietary phosphate absorption, such as use of phosphate binders alone, have minimal, if any, effects on serum phosphate levels. [45][46][47] Furthermore, serum phosphate levels are at their nadir in the morning and peak in the afternoon, when the largest differences in serum phosphate levels across a spectrum of dietary phosphate loads are noted. 48,49 Because the normal diurnal rhythm in serum phosphate levels is preserved in CKD, [48][49][50][51] studies that only measured morning fasting serum phosphate levels may have missed meaningful changes that might have been detected if phosphate was measured later in the day.…”
Section: Serum Phosphatementioning
confidence: 99%
“…Prior studies attempted to test the hypothesis that phosphate-and FGF23-lowering interventions would improve intermediate CVD endpoints, including LVH, vascular dysfunction, and vascular calcification. 45,47,55,89 However, no pilot study has tested whether the combination of phosphate binders and nicotinamide will have beneficial effects on markers of bone and mineral metabolism and on intermediate endpoints of CVD and CKD progression in patients with CKD stages 3-4. The results from such a study will help identify which of the tested surrogate markers should be advanced as the primary endpoints to a larger randomized study to test the utility of phosphate and FGF23 lowering on intermediate endpoints of CVD, renal, and skeletal risks (Figure 1).…”
Section: Possible Intermediate Endpointsmentioning
confidence: 99%
“…We and others have demonstrated increased circulating levels of pathogenic CKD-MBD factors (e.g., FGF23, Dkk1, sclerostin, activin-A) in humans with stage 2–3 native CKD versus no CKD (11, 14) and in kidney transplant recipients with chronic allograft injury versus normal transplant biopsies (84), suggesting they may play an important role as functional biomarkers of the early CKD-MBD in both native and transplant CKD. However, other studies have reported significant variability in circulating levels of these factors across the spectrum of native and transplant CKD, cautioning against their use as reliable biomarkers in humans at present (22, 78, 85, 86).…”
Section: Application Of Emerging Concepts In the Ckd-mbd To Kidney Trmentioning
confidence: 83%